THE USE OF THARIQAH SAMIYYAH SYAFAWIYAH WITH PLOTAGON STORY MEDIA TO IMPROVE STUDENTS MAHARAH ISTIMA AT SDS IT AL MANAR TAKENGON - Luthfiah Bengi; Salma Hayati (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
This study aims to determine the effectiveness of using thariqah sam'iyyah shafawiyah with Plotagon Story media to improve maharah istima' of fourth grade students of SDS IT Al-Manar Takengon, Aceh Tengah. This study is motivated by the low ability of students' istima' and not maximizing the use of appropriate learning methods and media. The research method used is quasi experiment with research design Non-equivalent Control Group Design. The data collection technique carried out in the form of a test using a multiple choice instrument of 20 questions. This instrument has been reviewed to ensure the accuracy in terms of content and language as well as testing the level of difficulty of the questions. The research subjects involves two classes: class IV-A as the experimental class and VI-B as the control class, each consisting of 25 samples. Data analysis was conducted using SPSS version 20 with normality test, homogeneity test, and independent sample T-test. The results showed that there was a significant difference after the use of thariqah sam'iyyah shafawiyah with Plotagon Story as the media. Thus, the application of appropriate methods and media that used in learning can help in achieving student learning outcomes